KONTEKSTUALISASI PEMAHAMAN ATAS HADIS (Studi Perbandingan Antara Orientalisme dan Oksidentalisme) - Taufiqur Rohman (IAIN Kediri, 2018)
This article aims at examining and analyzing contextually and critically the understanding on hadith as a comparison study between orientalism and Occidentalism’s understanding. The hadith understanding both critically and contextually has been existed and will continuously exist doing by whoever included orientalist and occidentalist which is considered fair as long as its has high objectivity and fulfill scientific research standard to avoid bias and personal purpose. The objectivity and scientific standard are such as commitment, can be tested and verified, trusted, objectivity, and can be used in general. Hadith contextualizing or the effort to interpret hadith based on its context and time is important to be done to answer the dynamic and progressive social reality. Keywords: Orientalist, occidentalist, objectivity, contextualization.